Mary and Maternal Health Decolonizing Luke 1–2 Amidst the Crisis of Teen Pregnancy - Ibita, Ma. Marilou S. (2024)
This study responds to the central question: ‘What do you see as the tasks, methods, and aims of New Testament studies, given the demands and priorities of the context in which you work?’ From a decolonizing perspective, biblical scholarship’s crucial role is fostering interdisciplinary approaches to help address 21st-century challenges set within the communal see-judge-act-evaluate-celebrate/ritualize framework. As a test case, this study characterizes Mary, her maternal health, and the perils of pregnancy in Luke 1–2 from a decolonizing angle within the context of the teenage pregnancy crisis in the Philippines. This decolonizing and interdisciplinary approach involves utilizing a synergy of contextual biblical hermeneutics in interpreting Luke 1–2 as an attempt to ensure that New Testament studies remain a relevant source of inspiration for actionable responses to promote teenage maternal health.
Keywords: see-judge-act-evaluate-celebrate/ritualize; maternal health; Mary; Luke 1–2; Decolonization; Contextual biblical hermeneutics